Population-based cancer screening programmes in low-income and middle-income countries: regional consultation of the International Cancer Screening Network in India. Issue 2 (February 2018) - Sivaram, Sudha; Majumdar, Gautam; Perin, Douglas; Nessa, Ashrafun; Broeders, Mireille; Lynge, Elsebeth; Saraiya, Mona; Segnan, Nereo; Sankaranarayanan, Rengaswamy; Rajaraman, Preetha; Trimble, Edward; Taplin, Stephen; et al.
Summary: The reductions in cancer morbidity and mortality afforded by population-based cancer screening programmes have led many low-income and middle-income countries to consider the implementation of national screening programmes in the public sector. Screening at the population level, when planned and organised, can greatly benefit the population, whilst disorganised screening can increase costs and reduce benefits. The International Cancer Screening Network (ICSN) was created to share lessons, experience, and evidence regarding cancer screening in countries with organised screening programmes. Organised screening programmes provide screening to an identifiable target population and use multidisciplinary delivery teams, coordinated clinical oversight committees, and regular review by a multidisciplinary evaluation board to maximise benefit to the target population. In this Series paper, we report outcomes of the first regional consultation of the ICSN held in Agartala, India (Sept 5–7, 2016), which included discussions from cancer screening programmes from Denmark, the Netherlands, USA, and Bangladesh. We outline six essential elements of population-based cancer screening programmes, and share recommendations from the meeting that policy makers might want to consider before implementation.